2017
DOI: 10.1002/bin.1483
|View full text |Cite
|
Sign up to set email alerts
|

Using differential reinforcement of a discard response to treat pica

Abstract: Previous research on the treatment of pica (i.e., the ingestion of inedible objects) is limited compared to research on the treatment of other types of severe problem behavior. This study involved the use of differential reinforcement of alternative behavior, with a discard response as the alternative behavior, to treat pica presented by a 13-year-old girl with an autism spectrum disorder. We extended previous research by thinning the schedule of reinforcement for the alternative response. Substantial reductio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 29 publications
(42 reference statements)
0
7
0
2
Order By: Relevance
“…DR was used in 12 studies and included reinforcing only the desired behaviour and using extinction to eliminate all other prior approximations. An example of DR is using preferred items, such as pretzels, to reinforce behaviours close to the desired behaviour, such as not approaching pica items (Slocum, Mehrkam, Peters, & Vollmer, 2017). When the desired behaviour is attained, reinforcement ends for all previous approximations of the desired behaviour.…”
Section: Resultsmentioning
confidence: 99%
“…DR was used in 12 studies and included reinforcing only the desired behaviour and using extinction to eliminate all other prior approximations. An example of DR is using preferred items, such as pretzels, to reinforce behaviours close to the desired behaviour, such as not approaching pica items (Slocum, Mehrkam, Peters, & Vollmer, 2017). When the desired behaviour is attained, reinforcement ends for all previous approximations of the desired behaviour.…”
Section: Resultsmentioning
confidence: 99%
“…If an individual is instructed to do something else at the moment they engage in a response that is predictive of pica, it may be as effective as blocking for some individuals and less restrictive. Previous research has shown that redirecting the individual to discard or exchange pica items is an effective intervention (Goh et al, ; Ricciardi et al, ; Schmidt et al, ; Slocum et al, ); however, this approach results in continued contact with potentially dangerous or contaminated items. An alternative strategy might be to prompt appropriate leisure activities or other responses that do not result in touching potential pica items, such as reporting the presence of those items to caregivers in exchange for other reinforcement.…”
Section: Discussionmentioning
confidence: 99%
“…For example, LeBlanc, Piazza, and Krug () demonstrated that blocking (i.e., immediately before the item passed the plane of the lips) was as effective as restraint in reducing pica. In addition, blocking often is included in treatment packages for pica, such as interrupting pica attempts and prompting a more appropriate behavior (Goh, Iwata, & Kahng, ; Hagopian, Gonzalez, Rivet, Triggs, & Clark, ; Ricciardi, Luiselli, Terrill, & Reardon, ; Schmidt et al, ; Slocum, Mehrkam, Peters, & Vollmer, ). For example, Hagopian et al used response blocking, as well as differential reinforcement of alternative behavior, to decrease automatically maintained pica by two teenagers.…”
mentioning
confidence: 99%
“…reinforcing consumption of appropriate edibles; Piazza et al 1996), (b) providing alternative and competing sources of reinforcement (i.e. noncontingent or contingent access to alternative reinforcers; Ing et al 2011), and (c) establishing alternative responses (such as discarding items) once the individual contacts pica items in the environment (Ricciardi et al 2003;Slocum et al 2017).…”
mentioning
confidence: 99%
“…Giving individuals the choice to engage in some response (and contact reinforcement through a contingency) is typically more preferred than interventions that do not (Luczynski and Hanley 2009), which could have implications for the course of treatment for pica. Recently, Slocum et al (2017) used a differential reinforcement procedure to teach a 13-year-old girl with autism spectrum disorder to engage in a discard response, which consisted of picking up and putting pica items in a nearby trashcan. This intervention resulted in large reductions in pica even when the schedule of reinforcement for the discard response was thinned.…”
mentioning
confidence: 99%